The floor of the Mukhachatushki of the Shiva Temple (Temple 3) - Temples of India Project Team (Jio Institute, 2024)
The floor of the mukhachatushki (four-faced entrance platform) of the Shiva Temple (Temple 3) shows marks of metal dowels, shedding light on the temple’s construction technique. Mortar was not used in these temples; instead, metal dowels were used to join the stone blocks and parts of the temple which provided the structural integrity of the entire edifice.